Gut microbiota and its role in human health - Rajilić-Stojanović, Mirjana (Array, 2018)
Humans live in a close association with a complex microbial ecosystem that is collectively termed microbiota. Microbiota is concentrated in the last part of the gastrointestinal tract, where it ferments undigested food residues and produces various metabolites that have a systemic influence on human physiology. The composition of microbiota is influenced by genetic and environmental factors that shape a unique ecosystem in each human. Despite considerable compositional variations, the functional output of the ecosystem is highly similar in all healthy individuals. Although it is still not possible to define normal microbiota, comparisons between patients suffering from a number of chronic diseases with unknown etiology and controls have shown that patients have specific, dysbiotic microbiota composition. While it still remains to be determined if the microbiota dysbiosis is an etiological factor or a consequence of a disease, these findings have initiated intensive microbiota research. Numerous proven functions of microbiota include contribution to the digestion,synthesis of essential metabolites (vitamins and amino acids) and the intensive crosstalk with the immune, the endocrine and the nervous system. Even though this field of research is still in an early stage, it is clear that microbial metabolites can have various effects on humans including directbeneficial effect, toxicity, but also more subtle interactions since microbial products can act as immune regulating or neuro-signaling molecules. The complex network of bidirectional interactionsbetween microbiota and humans is unexplored but highly potent for development of novel strategies to preserve and improve health.